2008
DOI: 10.1016/j.devcel.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

dGRASP-Mediated Noncanonical Integrin Secretion Is Required for Drosophila Epithelial Remodeling

Abstract: Integral plasma membrane proteins are typically transported in the secretory pathway from the endoplasmic reticulum and the Golgi complex. Here we show that at specific stages of Drosophila development corresponding to morphological changes in epithelia, apposed basolateral membranes separate slightly, allowing new plasma membrane contacts with basal extracellular matrix. At these sites, newly synthesized integrin alpha subunits are deposited via a mechanism that appears to bypass the Golgi. We show that the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
198
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(212 citation statements)
references
References 60 publications
13
198
0
1
Order By: Relevance
“…In stage 11, they rapidly become squamous, doubling their apical and basal areas and trebling their perimeters in 20 min. Whereas external forces drive this squamous expansion as nurse cells empty their contents into the oocyte, the FCs must nevertheless actively remodel their junctions and membrane domains to maintain adhesion to the extracellular matrix (Delon and Brown, 2009;Schotman et al, 2008), cell-cell adhesion (Pope and Harris, 2008) and epithelial integrity. Because optical constraints make it difficult to image squamous cells in cross-section, we employed maximal projections encompassing the apical junctions and apical surface (see Materials and Methods and supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In stage 11, they rapidly become squamous, doubling their apical and basal areas and trebling their perimeters in 20 min. Whereas external forces drive this squamous expansion as nurse cells empty their contents into the oocyte, the FCs must nevertheless actively remodel their junctions and membrane domains to maintain adhesion to the extracellular matrix (Delon and Brown, 2009;Schotman et al, 2008), cell-cell adhesion (Pope and Harris, 2008) and epithelial integrity. Because optical constraints make it difficult to image squamous cells in cross-section, we employed maximal projections encompassing the apical junctions and apical surface (see Materials and Methods and supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used an available FRT-recombined allele, pak 14 (Newsome et al 2000), which encodes a protein two amino acids shorter than that encoded by pak 6 , to make follicle cell clones (FCC) lacking pak (marked by the absence of GFP), and assessed the distribution of RhoGEF2 using an antiRhoGEF2 antibody. In wild-type egg chambers Rho-GEF2 was enriched throughout oogenesis to the basal end of follicle cells, including at the basolateral domain between follicle cells in stage 10B egg chambers, which parts as follicle cells flatten to accommodate growth of the oocyte ( Figure 5, A9-D9) (Schotman et al 2008). During early oogenesis loss of Pak had little or no effect on RhoGEF2 ( Figure 5A$), whereas pak 14 FCCs in stage 10A or older egg chambers showed delocalization of RhoGEF2 such that it was no longer basally restricted or highly enriched at the basolateral junction as seen in the neighboring wild-type cells, but rather was distributed throughout the cell ( Figure 5, B$-D$).…”
Section: Resultsmentioning
confidence: 99%
“…RhoGEF2 is enriched at the basal end of the follicle cells throughout oogenesis including the points of basal membrane separation between follicle cells that occurs during follicle cell flattening in late stage egg chambers (Schotman et al 2008). Recently, it was shown that the Rho1 actomyosin contractility pathway is required for this separation between follicle cells at the basal membrane and presumably this signaling is activated by RhoGEF2 (Schotman et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…GRASP55 binds and may facilitate transport of the transmembrane growth factor ␣ (Kuo et al, 2000), and both GRASP proteins bind members of the p24 protein family, thereby inhibiting p24 recycling to the ER (Barr et al, 2001). The GRASP homologues in Dictyostelium and Drosophila melanogaster, both of which organisms have one rather than two GRASP proteins, do not organize the nonlinked Golgi but rather contribute to unconventional secretion (Kinseth et al, 2007;Schotman et al, 2008), suggesting that linking of Golgi cisternae may be a later step in the evolutionary development of these proteins. Whether these selective transport functions of the GRASP protein constitute an inseparable part of its structural function, e.g., in membrane tethering, or whether selective transport represents a second and distinct function remains a compelling and unanswered question.…”
Section: Discussionmentioning
confidence: 99%